The role of clinical-anamnestic indices in diagnostics of severe persisting bronchial asthma in children - Khilchevska, V. S.; Kolyubakina, L. V. (Journal of Education, Health and Sport, 2017)
Khilchevska V. S., Kolyubakina L. V. The role of clinical-anamnestic indices in diagnostics of severe persisting bronchial asthma in children. Journal of Education, Health and Sport. 2017;7(1):293-299. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.260199 http://ojs.ukw.edu.pl/index.php/johs/article/view/4199 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 754 (09.12.2016). 754 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2017; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.01.2017. Revised 16.01.2017. Accepted: 24.01.2017. THE ROLE OF CLINICAL-ANAMNESTIC INDICES IN DIAGNOSTICS OF SEVERE PERSISTING BRONCHIAL ASTHMA IN CHILDREN V. S. Khilchevska, L. V. Kolyubakina Higher State Educational Establishment of Ukraine «Bukovinian State Medical University», Chernivtsi, Ukraine Abstract Performed integral estimation of the diagnostic value of the obtained clinical-paraclinical parameters is indicative of a sufficient amount of reliable markers in verification of severe bronchial asthma (BA) in children. Children with severe bronchial asthma are characterized by the following phenotype peculiarities: early debut of the disease (chance ratio (CR) = 1,5 (95% confidence interval (CI) 0,9-2,7), comorbid allergic diseases available (allergic rhinitis and atopic dermatitis) (CR 2,7 (95% CI 1,5-4,8) and drug-induced or comorbid drug-induced and food or domestic allergy (CR=4,8 (95% CІ 0,1-36,5)), infectious index more than 2 (CR=3,3 (95% CІ 1,6-6,7), seasonal exacerbation of BA mainly from November to March (СR=2,7 (95% CІ 1,5-4,9), associated with a trigger role of acute respiratory viral infection (ARVI) (СR=5,5 (95% CІ 2,4-12,6) and meteorological factors (СR=3,8 (95% CІ 0,4-36,4). Key words: children, bronchial asthma, clinical-anamnestic indices, sensitivity, specificity.